STUDI PERFORMA PEMANEN ENERGI PIEZOELEKTRIK DENGAN METODE VORTEX INDUCED VIBRATION - Gamayel, Adhes (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Piezoelectric energy harvesters (PEHs) convert mechanical energy into electricity. They operate based on pressure or vibration. One method for inducing vibration in PEHs is vortex-induced vibration (VIV), which harnesses wind energy using a bluff body. In this study, the researchers investigated the output voltage generated by PEHs at different altitudes, specifically 6.25 cm and 12.5 cm. Both experimental and simulation approaches were employed. The experimental setup included a PEH composed of a piezoelectric bimorph and a rectangular-trapezoid substrate. Wind speeds of 5, 7, and 9 m/s were tested in a wind tunnel with a cross-section of 250 mm x 250 mm. The simulation utilized the finite element method to explore wind flow patterns. Notably, the results revealed that PEHs positioned at an altitude of 6.25 cm generated higher voltages than those at 12.5 cm. At an altitude of 6.25 cm, each wind speed's maximum electrical voltage values are 4.18 volts, 4.67 volts, and 5.13 volts, respectively. The maximum electric voltage value at a height of 12.5 cm for each wind speed is 2.1 volts, 3.94 volts, and 4.44 volts, respectively. This phenomenon is attributed to the narrowing of the wind tunnel’s inlet area due to the presence of a bluff body, leading to increased air velocity along the tunnel walls. Consequently, a vortex forms near the square bluff body, resulting in pressure fluctuations that induce PEH vibration and generate voltage.